Genetic code expansion as a tool to study regulatory processes of transcription - Schmidt, Moritz J.; Summerer, Daniel (Frontiers in Chemistry, 2014)
The expansion of the genetic code with noncanonical amino acids (ncAA) enables the chemical and biophysical properties of proteins to be tailored, inside cells, with a previously unattainable level of precision. A wide range of ncAA with functions not found in canonical amino acids have been genetically encoded in recent years and have delivered insights into biological processes that would be difficult to access with traditional approaches of molecular biology. A major field for the development and application of novel ncAA-functions has been transcription and its regulation. This is particularly attractive, since advanced DNA sequencing- and proteomics-techniques continue to deliver vast information on these processes on a global level, but complementing methodologies to study them on a detailed, molecular level and in living cells have been comparably scarce. In a growing number of studies, genetic code expansion has now been applied to precisely control the chemical properties of transcription factors, RNA polymerases and histones, and this has enabled new insights into their interactions, conformational changes, cellular localizations and the functional roles of posttranslational modifications.